2021
DOI: 10.1007/s00300-021-02822-7
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of marine non-indigenous species on Svalbard by DNA metabarcoding of sediment

Abstract: Non-indigenous species (NIS) in the Arctic have an increased likelihood of arrival from ship traffic in the region, while the survival potential of the species becomes more likely in a warming environment. Monitoring is essential to detect the rate and magnitude of the establishment of NIS. In this study, a list of 123 potential marine NIS for Svalbard was drafted and the presence of marine NIS in soft sediment of Kongsfjorden in Svalbard was assessed using molecular metabarcoding techniques. For 37 species, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
0
13
0
Order By: Relevance
“… Casey et al (2021) have shown how the choice of genetic barcode marker for metabarcoding can produce a skewed picture of metazoan diversity. A particularly striking example of this was our detection of only two species of nematodes in Kongsfjord, whereas van den Heuvel-Greve et al (2021) detected 33 species using 18S primers, but only one with CO1. Even 33 may seem like a small number, considering the proposition that Kongsfjord has more than hundred species of nematodes as identified by morphology ( Somerfield et al, 2006 ).…”
Section: Discussionmentioning
confidence: 86%
“… Casey et al (2021) have shown how the choice of genetic barcode marker for metabarcoding can produce a skewed picture of metazoan diversity. A particularly striking example of this was our detection of only two species of nematodes in Kongsfjord, whereas van den Heuvel-Greve et al (2021) detected 33 species using 18S primers, but only one with CO1. Even 33 may seem like a small number, considering the proposition that Kongsfjord has more than hundred species of nematodes as identified by morphology ( Somerfield et al, 2006 ).…”
Section: Discussionmentioning
confidence: 86%
“…the Mytilus complex), the lack of information on microscopic IAS, such as parasites, fungi and microalgae and the lack of knowledge on marine biota, particularly in the Arctic (Deb & Bailey, 2023), significantly hampers monitoring and surveillance programmes (Hughes et al., 2020). Recent advances in environmental DNA metabarcoding techniques are now enabling the early detection of some marine IAS in the Arctic (van den Heuvel‐Greve et al., 2021; Ware et al., 2016), although ground‐truthing and repeated sampling is still required to determine whether these species will survive, become established and subsequently cause any impact.…”
Section: Discussionmentioning
confidence: 99%
“…Paralithodes camtschaticus , apart from carrying an amphipod parasite, may also indirectly transmit trypanosome infections to wild cod populations (Hemmingsen et al., 2005). Both crab species have been recorded in other Arctic regions (Chan et al., 2018; van den Heuvel‐Greve et al., 2021), having been initially introduced to the Barents Sea in the 1960s and 1970s from its native range in the North Pacific with the intention of developing a fishery (Jørgensen et al., 2004). The snow crab Chionoecetes opilio was also introduced to the Barents Sea and has similarly expanded its range with some singular sightings from Svalbard, including a record from the northwest coast (Lorentzen et al., 2018), which may have originally resulted from a catch discard.…”
Section: Discussionmentioning
confidence: 99%
“…However, pelagic eDNA studies from elsewhere in the Arctic region are still missing. Benthic communities have only been characterized with sediment eDNA in Kongsfjorden (Svalbard) for NIS detection (van den Heuvel-Greve et al, 2021), and in the Beaufort Sea (Alaska, Barrow). In the latter study, DNA metabarcoding was used to investigate sea ice and sediment samples for metazoan diversity throughout winter, spring and summer (Leasi et al, 2021).…”
Section: Prospects For Edna In a Changing Oceanmentioning
confidence: 99%